2021
DOI: 10.3892/ijo.2021.5223
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone concentration regulates activin receptor-like kinase-2/3 expression levels with opposing effects on ovarian cancer cell survival

Abstract: Anti-Müllerian hormone (AMH) type II receptor (AMHRII) and the AMH/AMHRII signaling pathway are potential therapeutic targets in ovarian carcinoma. Conversely, the role of the three AMH type I receptors (AMHRIs), namely activin receptor-like kinase (ALK)2, ALK3 and ALK6, in ovarian cancer remains to be clarified. To determine the respective roles of these three AMHRIs, the present study used four ovarian cancer cell lines (COV434-AMHRII, SKOV3-AMHRII, OVCAR8, KGN) and primary cells isolated from tumor ascites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“… 15 , 16 , 17 Conversely, recent reports have shown that AMH promotes gynecologic cancer cell growth and migration, 18 and several anti‐AMHR2 antibodies have been demonstrated to exert tumor suppressive function on OC. 19 , 20 As BMPs share type I receptors with AMH, 1 BMP signaling may have an influence on gynecologic cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 , 17 Conversely, recent reports have shown that AMH promotes gynecologic cancer cell growth and migration, 18 and several anti‐AMHR2 antibodies have been demonstrated to exert tumor suppressive function on OC. 19 , 20 As BMPs share type I receptors with AMH, 1 BMP signaling may have an influence on gynecologic cancer.…”
Section: Introductionmentioning
confidence: 99%